Pengaruh Gross Profit Margin Dan Net Profit Margin Terhadap Harga Saham Pada Perusahaan Sektor Pertambangan Yang Terdaftar Di Jakarta Islamic Index (JII) Tahun 2019-2022 - Puspita Sari; Faturrahman Faturrahman; Nurrahma Sari Putri (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This thesis aims to determine the effect of gross profit margin and net profit margin on stock prices in mining sector companies listed on the jakarta islamic index for 2019-2022. This study uses the indenpedent variables, namely gross profit margin and net profit margin. the dependent variable is stock price. the data used in this study is secondary data, namely in the form of financial reports of sharia companies registered on the jakarta islamic index in 2019-2022. This research is descriptive with a quantitative approach. Statistical methods using multiple linear regression analysis, t test, f test and analysis of the coefficient of determination. The results of this study indicate that the ratio of gross profit margin and net profit margin has an effect on stock prices. By using the f test it is found that the independent variables have a simultaneous influence on the dependent variables. Calculation of the coefficient of determination shows thet all independent variables, namely gross profit margin and net profit margin, can explain the stock price variable by 30% the remaining 70% is influenced by other variables not examined in this study.